Targeting PFKFB3 radiosensitizes cancer cells and suppresses homologous recombination - Nina M. S. Gustafsson (Nature Portfolio, 2018)
Targeting the glycolytic PFKFB3 enzyme is being studied as a therapeutic strategy against cancer. Here the authors identify PFKFB3 as being involved in homologous recombination (HR) repair of DNA double strand breaks (DSBs) and present a PFKFB3 inhibitor.